2011
DOI: 10.1111/j.2042-3306.2010.00306.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal dexamethasone treatment in late gestation induces precocious fetal maturation and delivery in healthy Thoroughbred mares

Abstract: Dexamethasone treatment could be used to improve foal viability in mares at risk of preterm delivery. The endocrine effects of such a therapy must be evaluated before clinical intervention with glucocorticoids can be recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 41 publications
4
27
0
1
Order By: Relevance
“…At delivery, placental area was smaller after maternal dexamethasone treatment, consistent with the known growth inhibitory effects of synthetic glucocorticoids on the placenta in other species [13,33]. In previous studies of dexamethasone administration, foal birthweight was also unaffected, although crown rump length was reduced at dexamethasone doses similar to those used here [6][7][8]. In previous studies of dexamethasone administration, foal birthweight was also unaffected, although crown rump length was reduced at dexamethasone doses similar to those used here [6][7][8].…”
Section: Foal Effectssupporting
confidence: 82%
See 1 more Smart Citation
“…At delivery, placental area was smaller after maternal dexamethasone treatment, consistent with the known growth inhibitory effects of synthetic glucocorticoids on the placenta in other species [13,33]. In previous studies of dexamethasone administration, foal birthweight was also unaffected, although crown rump length was reduced at dexamethasone doses similar to those used here [6][7][8]. In previous studies of dexamethasone administration, foal birthweight was also unaffected, although crown rump length was reduced at dexamethasone doses similar to those used here [6][7][8].…”
Section: Foal Effectssupporting
confidence: 82%
“…In particular, there are changes in glucose metabolism in the adult offspring, which are due, in part, to altered secretion and action of insulin [12][13][14]. However, nothing is known about the metabolic consequences of dexamethasone treatment of pregnant horses either for the mare or her foal after birth, although there are changes in maternal progestagen concentrations and adrenocortical function of the newborn foal after dexamethasone administration to pregnant mares near term [8]. This study, therefore, examined pancreatic b cell function in pregnant mares and their foals after birth following dexamethasone administration in late gestation.…”
Section: Introductionmentioning
confidence: 99%
“…The maternal pregnane rise in response to fetal ACTH administration occurred only after days, a time frame more consistent with an indirect placental response than a result of a direct stimulation of fetal adrenal pregnenolone secretion by ACTH. More importantly, fetal [135] and maternal [136] administration of glucocorticoid had the same effect, increasing maternal pregnane concentrations. Given that glucocorticoid administration actually suppresses fetal adrenal steroid secretion [136], the increase in maternal pregnane induced by fetal ACTH and glucocorticoid treatments more likely reflects a direct corticoid effect on the placenta rather than an increase in fetal adrenal pregnenolone secretion.…”
Section: The Feto-placental Unitmentioning
confidence: 74%
“…More importantly, fetal [135] and maternal [136] administration of glucocorticoid had the same effect, increasing maternal pregnane concentrations. Given that glucocorticoid administration actually suppresses fetal adrenal steroid secretion [136], the increase in maternal pregnane induced by fetal ACTH and glucocorticoid treatments more likely reflects a direct corticoid effect on the placenta rather than an increase in fetal adrenal pregnenolone secretion. In vitro studies leave additional doubt as to the ability of the equine fetal adrenal to [196] and Wesson and Ginther [113].…”
Section: The Feto-placental Unitmentioning
confidence: 74%
“…The foals from both mare groups appeared mature, and there were no significant differences in immune status, behavioral responses, and hematological parameters except for the crown-rump length, which was lower than control foals. The authors concluded that the results, although encouraging, indicated that further work would be necessary to identify the benefits to fetal health of synthetic glucocorticoid therapy in sick pregnant mares [54].…”
Section: Prematuritymentioning
confidence: 89%